Penetration by Botryosphaeriaceae species in avocado, guava and persimmon fruit during postharvest - Ludwig Navarro, Barbara; Edwards Molina, Juan Pablo; Nogueira Júnior, Antonio F. (Wiley, 2021)
Botryosphaeriaceae species have a wide host range and a worldwide distribution. These fungal species can colonize several plant organs, such as the trunk, leaves and fruit. Some Botryosphaeriaceae species cause important diseases on persimmon, avocado and guava fruit. However, there is a lack of information regarding the mechanisms of penetration by Botryosphaeriaceae species on these tropical and subtropical fruits. This study aimed to better understand the mechanisms involved in fungal penetration, host specificity and aggressiveness of Botryosphaeria dothidea, Lasiodiplodia pseudotheobromae and Neofusicoccum parvum on avocado (Persea americana), guava (Psidium guajava) and persimmon (Diospyros kaki) fruit. Scanning electron microscopy (SEM) image analysis showed that in avocado fruit, the three studied Botryosphaeriaceae species penetrated through lenticels. In guava fruit, penetration through stomata was verified for Botryosphaeria dothidea and Neofusicoccum parvum. In persimmon fruit, an appressoria-like structure was observed for B. dothidea, which suggests direct penetration. Disease incidence in wounded fruit was 24% higher than in non-wounded fruit. L. pseudotheobromae and N. parvum showed differences in aggressiveness in guava fruit. The longest incubation period was observed for N. parvum inoculated on guava, with an average of 4.5 days, and the shortest incubation period was verified for B. dothidea inoculated on avocado, with an average of 2.8 days. The area under the disease progress curve (AUDPC) did not differ between Botryosphaeriaceae species on avocado, whereas on guava and persimmon fruit, the AUDPC was lower for B. dothidea. The information regarding penetration mechanisms and aggressiveness is important to improve postharvest disease control strategies.